Psychomemory in Serat Panji: Overcoming Mental Health with a Local Wisdom Approach - Camelia, Ika Anggun; Utami, Respati Retno; Susanti, Arik; Asteria, Prima Vidya; Sampurno, M.Bayu T (Technium Social Sciences Journal, 2025)
Mental health is a common problem in the world community, especially in adolescents. 60% of students according to data from the American College Health Association are reported to be depressed. Likewise in Indonesia. Mental health problems often arise due to changes in social and lifestyle. So there is a need for an approach to overcome mental health problems. The research method uses a type of qualitative research with a content analysis approach of local culture because this study aims to analyze Panji fibers using psychomemory theory. "Serat Panji" is one of the local Indonesian cultural artifacts that tells the story of mental health disorders in the main character, but with the wisdom of the main character, mental health that starts from trauma can be solved with wise solutions. This research explores how an approach that can solve mental health problems using Psychomemory theory. Understanding and healing trauma requires courage to face and remember the events that caused it. Local culture-based approaches provide new ways to improve self-regulation and psychological resilience. This not only creates a holistic solution but also increases appreciation for cultural heritage. Understanding Panji's story through psychomemory theory helps us see how this story is more than just a narrative but it is an important tool in maintaining and reinforcing cultural identity through collective memory.